Assessment of healthy lifestyle behaviors after coronary artery bypass surgery - Semiha Alkan; Esengül Topal; Muhammet Onur Hanedan; İlker Mataracı (KARE Publishing, 2018)
Objective: After coronary artery bypass graft (CABG) surgery, there is a disease management process that patients should follow, and healthy behaviors play a key role in this process. The aim of this study was to evaluate the health-promoting behaviors of patients after CABG surgery and to determine the influential factors. Methods: This was a cross-sectional study of 152 patients who were admitted to the polyclinic between March and June 2016 and underwent a CABG procedure. The data were collected using a patient information form and the Health-Promoting Lifestyle Profile (HPLP). Number, percentage, SD, mean, independent t and analysis of variance tests were used to evaluate and describe the data. Results: The mean age of the patients in the study was 58+-13.71 years. Of the total, 6% of the patients were male, 55.4% stated that they had the CABG surgery between 1 and 4 months prior, and 88.4% went to check-ups regularly after discharge. The mean HPLP score of the enrolled patients was 110.28+-17.32. The patients who were under 55 years of age, married, had a comfortable income, no comorbid disease, those who underwent the CABG surgery between 1 and 4 months earlier, went to follow-up regularly after discharge, and those who were educated about their disease had a higher HPLP score (p<0.05). Conclusion: This study found that patients who underwent CABG surgery had a moderate HPLP score and that training on health-promoting behaviors at discharge had a positive effect on their implementation.